Porous metal tube loaded high-entropy alloy hydrogen permeation membrane as well as preparation method and application thereof
By spraying molybdenum and copper-doped cobalt-ferrochrome nickel high-entropy alloys on porous metal tubes, the existing dense metal hydrogen permeable films lack corrosion resistance and thermal stability when treating coke oven gas containing sulfur/carbon impurity gases, achieving efficient and low-cost hydrogen extraction.
Patent Information
- Application Number
- CN202510101549.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-05-02
AI Technical Summary
The existing dense metal hydrogen permeable membranes have poor corrosion resistance and poor thermal stability when treating coke oven gas containing sulfur/carbon impurity gas, and rely on precious metal palladium, which has scarce resources and high production costs.
A high-entropy alloy hydrogen permeable film loaded by porous metal tubes is used to improve hydrogen permeability and corrosion resistance by doping molybdenum and copper into cobalt-ferrochrome-nickel high-entropy alloys, and a film layer is prepared by supersonic thermal spraying film making method.
It realizes efficient extraction of hydrogen under mild conditions, with the purity of hydrogen products greater than 99.999%, and reduces the cost of raw materials, avoids the dependence of precious metals, and improves the thermal stability of the membrane.
Smart Images

Figure CN119913449A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen permeable membranes, and in particular to a high-entropy alloy hydrogen permeable membrane supported by a porous metal tube, and a preparation method and application thereof. Background Art
[0002] The development of hydrogen energy requires solving the problem of large-scale, low-cost, green, low-carbon and sustainable production of hydrogen. At present, the production methods of hydrogen include fossil fuel hydrogen production, water electrolysis hydrogen production, and industrial by-product gas hydrogen extraction. Extracting hydrogen from low-value industrial by-product gases, such as coke oven gas, chlor-alkali industrial tail gas, blast furnace gas, etc., can help reduce the cost of hydrogen production, improve resource utilization, reduce dependence on fossil fuels, and reduce greenhouse gas emissions. It has great development potential. Coke oven gas is a typical low-value industrial by-product gas with a hydrogen content of up to 54vol.% to 60vol.%, but at present, except for a small amount of coke oven gas used as synthesis gas, it is basically used for direct combustion and has not been fully utilized. If the rich hydrogen in coke oven gas can be extracted, a large amount of hydrogen can be provided for hydrogen energy and catalytic hydrogenation reactions. At present, hydrogen extraction from coke oven gas generally uses pressure swing adsorption, but the equipment investment is large, the energy consumption is high, and the purity of hydrogen products is low.
[0003] Membrane separation method for hydrogen extraction is favored due to its advantages of compact equipment, small footprint, high energy efficiency and high purity of hydrogen products. Membrane separation materials mainly include dense metal membranes, dense ceramic membranes, inorganic porous membranes, organic polymer membranes, graphene membranes, metal organic framework membranes, covalent organic framework membranes and hydrogen bonded organic framework membranes. Among them, dense metal membranes have become the focus of research due to their good high temperature thermal stability, mechanical properties and hydrogen selectivity.
[0004] The commonly used dense metal hydrogen permeable membrane is a palladium alloy membrane. In order to prevent the palladium alloy membrane from undergoing hydride phase change and hydrogen embrittlement at low temperatures, the working temperature is generally higher than 450°C. However, coke oven gas contains CH4 23vol.%~27vol.%, other hydrocarbons 2vol.%~3vol.%, CO 5vol.%~8vol.%, CO21vol.%~3vol.%, and a certain amount of sulfur-containing compounds such as H2S, CS2, COS, thiophene, mercaptan and sulfide. At high temperatures, these impurity gases decompose on the surface of palladium alloy to produce sulfur and carbon atoms, which passivate the palladium alloy and even poison it, especially sulfur poisoning, which seriously deteriorates the hydrogen permeability of palladium alloy. In addition, for supported hydrogen permeable membranes, the mutual diffusion of atoms between the palladium alloy membrane and the porous metal tube support will lead to a decrease in hydrogen permeability. Moreover, precious metal resources such as palladium are scarce, difficult to mine, and have high production costs, so dependence on precious metals should be minimized. Other dense metal membranes, such as vanadium membranes, niobium membranes, and tantalum membranes, also have difficulty solving the hydrogen embrittlement problem and the atomic interdiffusion problem between the porous metal tube support. Therefore, for hydrogen extraction from coke oven gas, it is urgent to develop a dense metal hydrogen permeable membrane that is suitable for mixed gases containing sulfur / carbon impurities, has good thermal stability, does not use precious metals, and can work efficiently under mild conditions. Summary of the invention
[0005] In order to overcome the shortcomings of the existing dense metal hydrogen permeable membrane technology, the purpose of the present invention is to provide a porous metal tube-loaded high entropy alloy hydrogen permeable membrane and a preparation method and application thereof, which solves the problems of poor sulfur / carbon resistance and poor thermal stability of conventional dense metal hydrogen permeable membranes.
[0006] To achieve the above objectives, the technical solution of the present invention is as follows.
[0007] A first aspect of the present invention provides a method for preparing a porous metal tube-supported high entropy alloy hydrogen permeable membrane, comprising the following steps:
[0008] Under an inert atmosphere, molybdenum and copper are mixed and ball-milled, and then cobalt, chromium, iron and nickel are added and mixed and ball-milled to obtain molybdenum- and copper-doped cobalt-chromium-iron-nickel high entropy alloy powders. Then, the molybdenum- and copper-doped cobalt-chromium-iron-nickel high entropy alloy powders are sprayed onto the surface of a porous metal tube by a supersonic thermal spraying film-making method to form a film layer, thereby obtaining a porous metal tube-loaded high entropy alloy hydrogen permeable membrane.
[0009] Technical principle of the present invention: The hydrogen permeable membrane of the present invention is made of a cobalt-chromium-iron-nickel high entropy alloy doped with molybdenum and copper. The hydrogen permeable membrane has good corrosion resistance by utilizing the structural lattice distortion effect, thermodynamic high entropy effect, dynamic hysteresis diffusion effect, and property harmonization effect generated by the high entropy of the alloy, and is suitable for extracting hydrogen from coke oven gas containing a lot of sulfur / carbon impurities. A small amount of molybdenum and copper are doped into the cobalt-chromium-iron-nickel high entropy alloy to expand the alloy lattice and improve its hydrogen permeability. The molybdenum and copper used to prepare the hydrogen permeable membrane are first mixed and ball-milled, and then mixed and ball-milled with cobalt, chromium, iron and nickel to reduce the particle size of the metal powder and fully alloy it, and then sprayed onto the surface of the porous stainless steel tube by supersonic thermal spraying to form a film, and the hydrogen permeable membrane has a uniform texture; the cobalt-chromium-iron-nickel high entropy alloy hydrogen permeable membrane and the porous metal tube support have similar thermal expansion coefficients, so that thermal stress will not be generated between the two at high temperatures to cause peeling; the cobalt-chromium-iron-nickel alloy hydrogen permeable membrane and the porous metal tube support have similar elemental composition, so that there will be no obvious atomic mutual diffusion between the two, and the performance of the hydrogen permeable membrane will not decrease due to changes in elemental composition; thus, the high entropy alloy hydrogen permeable membrane has good thermal stability.
[0010] Since molybdenum has a relatively large hardness, if all raw metal powders are mixed and ball-milled together, it is difficult to grind molybdenum finely, and molybdenum cannot form a uniform solid solution alloy with other metals through ball milling. Based on this, the present invention first mixes molybdenum and copper for ball milling, and uses the grinding aid effect of copper to grind molybdenum finely; then mixes and ball mills with other metals, which helps to fully alloy multiple metals during the ball milling process.
[0011] Preferably, the atomic percentage of molybdenum and copper in the raw materials is 2 at.% to 4 at.%, and more preferably 3 at.%.
[0012] Preferably, the mixing of molybdenum and copper is ball-milled for 30 hours to 60 hours, and the ball-milling speed is 420 r / min to 600 r / min. More preferably, the ball-milling time is 50 hours, and the ball-milling speed is 540 r / min.
[0013] Preferably, the atomic percentage of cobalt, chromium, iron and nickel in the raw material is 14.1 at.% to 32.9 at.%, and more preferably, the atomic percentage of cobalt, chromium, iron and nickel in the raw material is 23.5 at.%.
[0014] Preferably, after molybdenum and copper are ball-milled, cobalt, chromium, iron and nickel are added and the ball-milling time is 20 to 35 hours, and the ball-milling speed is 420 to 600 r / min. More preferably, the ball-milling time is 30 hours, and the ball-milling speed is 540 r / min.
[0015] Preferably, the porous metal tube is a porous Inconel 600 stainless steel tube with a wall thickness of 0.9 mm ± 0.1 mm, an average pore diameter of pores in the wall of 0.7 μm ± 0.1 μm, and a porosity of 55% to 65%.
[0016] Preferably, in the process of forming the membrane layer, the average membrane thickness of the high entropy alloy hydrogen permeable membrane is controlled to be 8μm±1μm. The present invention controls the average membrane thickness of the high entropy alloy hydrogen permeable membrane loaded by the porous metal tube to be 8μm±1μm by adjusting the powder feeding amount and the spraying time. For example, when the outer diameter of the porous metal tube is 6mm and the length is 50mm, the appropriate powder feeding amount is 1g / min and the spraying time is 3min, so that the average membrane thickness of the high entropy alloy hydrogen permeable membrane loaded by the porous metal tube can be controlled to be 8μm.
[0017] The second aspect of the present invention provides a porous metal tube-supported high entropy alloy hydrogen permeable membrane, which is prepared by the method for preparing the porous metal tube-supported high entropy alloy hydrogen permeable membrane described in the first aspect.
[0018] The third aspect of the present invention provides an application of the high entropy alloy hydrogen permeable membrane supported by a porous metal tube as described in the second aspect in extracting hydrogen from coke oven gas.
[0019] The high entropy alloy hydrogen permeable membrane of the present invention is used to extract hydrogen from coke oven gas at 300°C, and the hydrogen permeation flux is 3.47 mol·m -2 ·s -1 ~5.82mol·m -2 ·s -1 , the hydrogen permeability coefficient is 0.88×10 -7 mol·m -1 ·s -1 ·Pa -0.5 ~1.47×10 -7 mol·m -1 ·s -1 ·Pa -0.5 The purity of the extracted hydrogen is greater than 99.999%.
[0020] Compared with the prior art, the porous metal tube-supported high entropy alloy hydrogen permeable membrane provided by the present invention has the following beneficial effects:
[0021] 1. The present invention adds a small amount of molybdenum and copper to the main elements of the high entropy alloy, cobalt, chromium, iron and nickel, to expand the lattice of the high entropy alloy, thereby improving the hydrogen permeability; and utilizes the strengthening effect produced by the high entropy of the alloy to make the prepared high entropy alloy hydrogen permeable membrane have good corrosion resistance, and is suitable for extracting hydrogen from coke oven gas containing a lot of sulfur / carbon impurities.
[0022] 2. The present invention first mixes molybdenum and copper and then mixes them with cobalt, chromium, iron and nickel to reduce the particle size of each metal powder and fully alloy them during the ball milling process. The high entropy alloy powder obtained by ball milling is then sprayed onto the surface of a porous metal tube by a supersonic thermal spraying film-making method to form a film, so that the prepared high entropy alloy hydrogen permeable membrane has a uniform texture and improves the hydrogen permeability.
[0023] 3. The present invention uses relatively low-priced metals such as cobalt, chromium, iron, nickel, molybdenum and copper to prepare high-entropy alloy hydrogen permeable membranes, and does not use rare metals with scarce resources and high production costs. On the basis of reducing raw material costs, the hydrogen permeability effect is improved, and the membrane is suitable for popularization and use.
[0024] 4. The cobalt-chromium-iron-nickel high entropy alloy hydrogen permeable membrane and the porous metal tube support of the present invention have similar thermal expansion coefficients, and no thermal stress will be generated between the two at high temperatures to cause peeling; the cobalt-chromium-iron-nickel high entropy alloy hydrogen permeable membrane and the porous metal tube support have similar elemental compositions, and there will be no obvious atomic mutual diffusion between the two, and the performance of the hydrogen permeable membrane will not decrease due to changes in elemental composition. Therefore, the high entropy alloy hydrogen permeable membrane has good thermal stability and can maintain stable hydrogen permeation flux during hydrogen extraction.
[0025] 5. The high entropy alloy hydrogen permeable membrane prepared by the present invention is a dense metal hydrogen permeable membrane, which is used to extract hydrogen from coke oven gas. The mass transfer of hydrogen in the high entropy alloy hydrogen permeable membrane conforms to the "atomic dissolution-diffusion" mechanism, and the hydrogen product has high purity. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a scanning electron microscope photograph of the high entropy alloy powder obtained by ball milling in Example 1.
[0027] Figure 2 It is the X-ray diffraction spectrum of the high entropy alloy powder obtained by ball milling in Example 1 and Comparative Example 1.
[0028] Figure 3 This is a transmission electron microscope photograph of the high entropy alloy hydrogen permeable membrane supported by the porous metal tube prepared in Example 1.
[0029] Figure 4 Schematic diagram of the hydrogen separator of Example 1 extracting hydrogen from coke oven gas. (A) is a schematic diagram of the hydrogen separator; (B) is a partial schematic diagram of the high entropy alloy hydrogen permeable membrane supported by the porous metal tube in (A) extracting hydrogen; (C) is a partial schematic diagram of the high entropy alloy hydrogen permeable membrane in (B) extracting hydrogen.
[0030] Figure 5 This is a flowchart of the process of extracting hydrogen from coke oven gas using a high entropy alloy hydrogen permeable membrane supported by a porous metal tube prepared in Example 1.
[0031] Figure 6It is a trend diagram of the hydrogen permeation flux of the porous metal tube-supported high entropy alloy hydrogen permeable membrane prepared in Examples 1 to 3 as a function of temperature.
[0032] Figure 7 The graphs are the curves showing the change of hydrogen permeation flux of the high entropy alloy hydrogen permeable membrane supported by the porous metal tube prepared in Example 1 and Example 2 over time. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0034] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0035] The technical solution of the present invention is further described below through specific embodiments.
[0036] In the following examples, the methods described are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0037] In the following embodiments, the purity of the raw metals cobalt, chromium, iron, nickel and copper is not less than 99.5wt%, and the powder particle size is less than 74μm; the purity of the raw metal molybdenum is not less than 99.5wt%, and the powder particle size is less than 5μm.
[0038] In the following embodiments, the rocking-planetary ball mill is ND8-1L, produced by Nanjing Nanda Tianzun Electronics Co., Ltd. The volume of the ball mill is 100 mL, the lining of the ball mill and the grinding balls are made of sintered zirconium dioxide, the ratio of the number of grinding balls with diameters of 9 mm, 5 mm and 3 mm is 20:40:40, and the mass ratio of grinding balls to materials after loading is about 60:1.
[0039] In the following embodiments, the ball mill loading and unloading operations are carried out in a glove box protected by argon gas. The glove box is a Lab2000 model produced by Etex Inert Gas Systems Co., Ltd. The purity of the argon gas is 99.999%, and the oxygen content in the glove box is <0.1ppm and the water content is <0.1ppm.
[0040] In the following embodiments, the wall thickness of the porous Inconel 600 stainless steel pipe is 0.9 mm, the average pore diameter of the pores in the wall is 0.7 μm, and the porosity is 60%.
[0041] In the following embodiments, the supersonic thermal spraying system is Inno-Pyramid HP / HVOF 5220, produced by Praxair Surface Technologies. The spraying process includes:
[0042] First, wash the porous metal tube with ethanol, blow it dry with hot air, and then install it on the supersonic thermal spray system, and then adjust the distance between the spray gun and the porous metal tube to 230mm. Load the high entropy alloy powder into the silo of the spray system. Adjust the ratio of oxygen and fuel propane to produce flames to 4:1, the oxygen pressure to 1.2MPa, the propane pressure to 0.6MPa, the powder feeding gas pressure to 1.3MPa, the powder feeding gas is argon, the argon purity is 99.999%, the pneumatic valve air pressure is 0.75MPa, the ignition hydrogen pressure is 0.35MPa, and the cooling water flow rate is 9L / min. By adjusting the powder feeding amount and spraying time, for example, when the porous metal tube has an outer diameter of 6mm and a length of 50mm, the appropriate powder feeding amount is 1g / min and the spraying time is 3min, so as to control the average membrane thickness of the hydrogen permeable membrane to 8μm.
[0043] Example 1
[0044] A method for preparing a high entropy alloy hydrogen permeable membrane supported by a porous metal tube comprises the following steps:
[0045] S1. In an argon-filled glove box, weigh the raw metals according to atomic percentage: cobalt 23.5 at.%, chromium 23.5 at.%, iron 23.5 at.%, nickel 23.5 at.%, molybdenum 3.0 at.%, copper 3.0 at.%, totaling 100.0 at.%.
[0046] S2. In an argon-filled glove box, put molybdenum and copper into a ball mill, and fill the ball mill with argon gas with a purity of 99.999% to 3 atm, and then ball mill on a rocking-planetary ball mill for 50 hours at a ball milling speed of 540 r / min to obtain MoCu metal powder after ball milling.
[0047] S3. In an argon-filled glove box, cobalt, chromium, iron and nickel are added to the ball mill containing the MoCu metal powder after ball milling in step S2, and argon with a purity of 99.999% is filled into the ball mill to 3 atm, and then ball milled on a rocking-planetary ball mill for 30 hours at a ball milling speed of 540 r / min to obtain CoCrFeNi-MoCu high entropy alloy powder.
[0048] S4. Using a supersonic thermal spraying film-forming method, the CoCrFeNi-MoCu high entropy alloy powder obtained in step S3 is sprayed onto the surface of a porous Inconel 600 stainless steel tube on a supersonic thermal spraying system to form a film layer, thereby preparing a CoCrFeNi-MoCu high entropy alloy hydrogen permeable membrane supported by a porous metal tube.
[0049] Example 2
[0050] A method for preparing a porous metal tube-supported high entropy alloy hydrogen permeable membrane, which differs from Example 1 in that the amount of molybdenum and copper in the raw material metals is reduced. The raw material metals are weighed according to atomic percentage: cobalt 24.0 at.%, chromium 24.0 at.%, iron 24.0 at.%, nickel 24.0 at.%, molybdenum 2.0 at.%, copper 2.0 at.%, a total of 100.0 at.%. The remaining operations are the same as those in Example 1, and a CoCrFeNi-MoCu high entropy alloy hydrogen permeable membrane supported by a porous metal tube is prepared.
[0051] Example 3
[0052] A method for preparing a porous metal tube-supported high entropy alloy hydrogen permeable membrane, which differs from Example 1 in that the amount of molybdenum and copper in the raw metals is increased. The raw metals are weighed according to atomic percentage: cobalt 23.0 at.%, chromium 23.0 at.%, iron 23.0 at.%, nickel 23.0 at.%, molybdenum 4.0 at.%, copper 4.0 at.%, a total of 100.0 at.%. The remaining operations are the same as those in Example 1, and a porous metal tube-supported CoCrFeNi-MoCu high entropy alloy hydrogen permeable membrane is prepared.
[0053] Comparative Example 1
[0054] A method for preparing a porous metal tube-supported high entropy alloy hydrogen permeable membrane, which differs from Example 1 in that molybdenum and copper are not added to the raw metals. The raw metals are weighed according to atomic percentage: 25.0 at.%, 25.0 at.%, 25.0 at.%, 25.0 at.%, and 100.0 at.%. The remaining operations are the same as those in Example 1, and a CoCrFeNi high entropy alloy hydrogen permeable membrane supported by a porous metal tube is prepared.
[0055] The CoCrFeNi-MoCu high entropy alloy powder obtained by ball milling in Example 1 was observed by scanning electron microscope using a Hitachi S4800 scanning electron microscope. Figure 1 shown.
[0056] Depend on Figure 1 It can be seen that the particle size of the CoCrFeNi-MoCu high entropy alloy powder obtained by ball milling in Example 1 is nanoscale, <100 nm.
[0057] The CoCrFeNi-MoCu high entropy alloy powder obtained by ball milling in Example 1 and the CoCrFeNi high entropy alloy powder obtained by ball milling in Comparative Example 1 were subjected to X-ray diffraction analysis using a SmartLab X-ray diffractometer from Rigaku Corporation of Japan, with Cu target Kα radiation, a scanning step of 0.01°, and a scanning speed of 2° / min. The X-ray diffraction spectrum is shown in FIG. Figure 2 shown.
[0058] Depend on Figure 2 It can be seen that the raw materials of Example 1 and Comparative Example 1 are alloyed into a single FCC crystal phase after high-intensity mechanical ball milling. In addition, due to the addition of molybdenum and copper to the raw materials of Example 1, the interplanar spacing of the crystals after ball milling is larger than that of Comparative Example 1, which is manifested as the diffraction peak shifting toward a low angle direction, which will be beneficial to the diffusion of hydrogen in the crystal.
[0059] The CoCrFeNi-MoCu high entropy alloy hydrogen permeable membrane supported by the porous metal tube prepared in Example 1 was observed by transmission electron microscopy using a JEM-2100F transmission electron microscope of a Japanese electronics company. The sample thickness was 50 μm. The transmission electron microscope photograph is shown in FIG. Figure 3 shown.
[0060] Depend on Figure 3 It can be seen that the CoCrFeNi-MoCu high entropy alloy hydrogen permeable membrane loaded by the porous metal tube prepared in Example 1 has a uniform texture and a thickness of 8 μm.
[0061] The CoCrFeNi-MoCu high entropy alloy hydrogen permeable membrane supported by the porous metal tube prepared in Examples 1 to 3 was used to extract hydrogen from coke oven gas, and the flow rate and purity of the extracted hydrogen were measured, and the hydrogen permeation flux and hydrogen permeation coefficient were calculated. For the convenience of description, the CoCrFeNi-MoCu high entropy alloy hydrogen permeable membrane supported by the porous metal tube is referred to as the high entropy alloy hydrogen permeable membrane below.
[0062] Performance test method of high entropy alloy hydrogen permeable membrane: referring to the main gas composition of industrial coke oven gas, high purity gases H2, CH4, CO, CO2, N2 and H2S are mixed to simulate coke oven gas, where the volume ratio of H2, CH4, CO, CO2 and N2 is 57:26:6:2:9, and the content of H2S is 0.2g / m 3 The performance of high entropy alloy hydrogen permeable membrane was tested by using simulated coke oven gas as gas raw material.
[0063] A hydrogen separator is assembled using a high entropy alloy hydrogen permeable membrane supported by a porous metal tube; the structure of the hydrogen separator is as follows Figure 4As shown, the hydrogen separator includes a shell and a plurality of porous metal tubes arranged in the shell, and each porous metal tube surface is loaded with a high entropy alloy hydrogen permeable membrane. The inlet gas of the hydrogen separator is H2-rich coke oven gas, wherein the H2 content is 57 vol.%, and the outlet gas of the hydrogen separator is H2-poor coke oven gas, wherein the H2 content is <10 vol.%.
[0064] The process of extracting hydrogen from coke oven gas using a hydrogen separator, such as Figure 5 As shown, the pressure at the air inlet of the hydrogen separator is set to 700 kPa, of which the hydrogen partial pressure is 399 kPa; the pressure at the hydrogen outlet is set to 100 kPa, and the flow rate of the extracted hydrogen can be read by a mass flow meter, and the hydrogen permeation flux and hydrogen permeation coefficient can be calculated based on the area of the high entropy alloy hydrogen permeable membrane, the hydrogen pressure on both sides of the membrane, and the membrane thickness.
[0065] The calculation formula of hydrogen permeation flux is:
[0066] J=F / A; wherein, J is the hydrogen permeation flux; F is the hydrogen flow rate; and A is the area of the high entropy alloy hydrogen permeable membrane.
[0067] The calculation formula of hydrogen permeability coefficient is:
[0068] Φ=J×L / (p1 0.5 -p2 0.5 ), where Φ is the hydrogen permeability coefficient; J is the hydrogen permeation flux; L is the thickness of the high entropy alloy hydrogen permeable membrane; p1 is the hydrogen partial pressure at the inlet of the hydrogen separator; and p2 is the hydrogen pressure at the outlet of the hydrogen separator.
[0069] The hydrogen permeation flux and hydrogen permeation coefficient of the high entropy alloy hydrogen permeable membranes of Examples 1 to 3 and Comparative Example 1 for extracting hydrogen from coke oven gas at 300° C. are measured, and the results are shown in Table 1. The hydrogen permeation flux of the high entropy alloy hydrogen permeable membranes of Examples 1 to 3 varies with temperature, as shown in Table 1. Figure 6 As shown; the hydrogen permeation flux of the high entropy alloy hydrogen permeable membrane of Example 1 and Example 2 changes with time, as shown Figure 7 shown.
[0070] Table 1 Effect of atomic percentage of molybdenum and copper on high entropy alloy hydrogen permeability membrane
[0071]
[0072] It can be seen from the data in Table 1 that, compared with the high entropy alloy hydrogen permeable membrane prepared in Comparative Example 1 without adding molybdenum and copper, the hydrogen permeation flux and hydrogen permeation coefficient of the high entropy alloy hydrogen permeable membrane prepared in Examples 1 to 3 by adding molybdenum and copper to the raw materials are relatively large, and with the increase of the atomic percentage of molybdenum and copper, the hydrogen permeation flux and hydrogen permeation coefficient show an increasing trend; and when too little molybdenum and copper are added to the raw materials, it is not conducive to improving the hydrogen permeability of the high entropy alloy hydrogen permeable membrane. This shows that doping molybdenum and copper in the cobalt-chromium-iron-nickel high entropy alloy is beneficial to improving the hydrogen permeability, which is mainly attributed to the increase in the interplanar spacing of the crystal after doping with molybdenum and copper.
[0073] Depend on Figure 6 It can be seen that as the temperature increases, the hydrogen permeation flux of the high entropy alloy hydrogen permeable membranes of Examples 1 and 2 increases, while the hydrogen permeation flux of Example 3 decreases, which indicates that the high entropy alloy hydrogen permeable membrane with excessive addition of molybdenum and copper has a larger hydrogen permeation flux at low temperatures, but is not conducive to hydrogen permeation at high temperatures. Figure 7 It can be seen that the hydrogen permeation flux of the high entropy alloy hydrogen permeable membranes of Example 1 and Example 2 is stable after running for 100 hours.
[0074] The composition of sulfur-free gas is analyzed by mass spectrometer, MALDI-TOF type, produced by Bruker Corporation of the United States; the composition of sulfur-containing compounds is analyzed by micro-sulfur spectrometer, HC-5 type, produced by Huashuo Technology Co., Ltd. The purity of hydrogen product can be calculated by taking the signal intensity of standard gas as reference. The signal intensity is expressed by integrated area; the purity is expressed by volume percentage.
[0075] The results show that the purity of hydrogen extracted from coke oven gas by the high entropy alloy hydrogen permeable membranes of Examples 1 to 3 at 300°C is greater than 99.999%, which indicates that the mass transfer of hydrogen in the high entropy alloy hydrogen permeable membrane conforms to the "atomic dissolution-diffusion" mechanism, and hydrogen molecules first dissociate into hydrogen atoms on the surface of the high entropy alloy hydrogen permeable membrane and then pass through the high entropy alloy hydrogen permeable membrane, while molecules and large atoms cannot pass through the high entropy alloy hydrogen permeable membrane, thereby making the high entropy alloy hydrogen permeable membrane have high hydrogen selectivity.
[0076] Example 4
[0077] A method for preparing a porous metal tube-supported high entropy alloy hydrogen permeable membrane, which differs from Example 1 in that the ball milling speeds in steps S2 and S3 are reduced to 420 r / min. The remaining operations are the same as those in Example 1 to prepare a high entropy alloy hydrogen permeable membrane.
[0078] Example 5
[0079] A method for preparing a porous metal tube-supported high entropy alloy hydrogen permeable membrane, which differs from Example 1 in that the ball milling speeds in steps S2 and S3 are reduced to 480 r / min. The remaining operations are the same as those in Example 1 to prepare a high entropy alloy hydrogen permeable membrane.
[0080] Example 6
[0081] A method for preparing a porous metal tube-supported high entropy alloy hydrogen permeable membrane is different from Example 1 in that the ball milling speeds in steps S2 and S3 are increased to 600 r / min. The remaining operations are the same as those in Example 1 to prepare a high entropy alloy hydrogen permeable membrane.
[0082] Example 7
[0083] A method for preparing a porous metal tube-supported high entropy alloy hydrogen permeable membrane, which differs from Example 1 in that the ball milling time of steps S2 and S3 is reduced to 30 hours and 20 hours respectively. The remaining operations are the same as those in Example 1, and a high entropy alloy hydrogen permeable membrane is prepared.
[0084] Example 8
[0085] A method for preparing a porous metal tube-supported high entropy alloy hydrogen permeable membrane, which differs from Example 1 in that the ball milling time of steps S2 and S3 is reduced to 40 hours and 25 hours, respectively. The remaining operations are the same as those in Example 1, and a high entropy alloy hydrogen permeable membrane is obtained.
[0086] Example 9
[0087] A method for preparing a porous metal tube-supported high entropy alloy hydrogen permeable membrane, which differs from Example 1 in that the ball milling time of steps S2 and S3 is increased to 60 hours and 35 hours, respectively. The remaining operations are the same as those in Example 1, and a high entropy alloy hydrogen permeable membrane is obtained.
[0088] In Example 1 and Example 4 to Example 9, high entropy alloy powders were obtained by ball milling at different ball milling speeds and ball milling times, and then high entropy alloy hydrogen permeable membranes were prepared. The prepared high entropy alloy hydrogen permeable membranes extracted hydrogen from coke oven gas at 300° C. The hydrogen permeation flux and hydrogen permeation coefficient are summarized in Table 2. The purity of the extracted hydrogen is greater than 99.999%.
[0089] Table 2 Effects of ball milling speed and ball milling time on high entropy alloy hydrogen permeable membrane
[0090]
[0091] From the data in Table 2, it can be seen that under the same ball milling time, when the ball milling speed is 420 r / minWhen the ball milling speed changes from 0.5 to 540 r / min, as the ball milling speed increases, the hydrogen permeation flux and hydrogen permeability coefficient of the high entropy alloy hydrogen permeable membrane obtained by the high entropy alloy powder after ball milling gradually increase, and further increasing the ball milling speed to 600 r / min is not conducive to further improving the hydrogen permeability of the high entropy alloy hydrogen permeable membrane. At the same ball milling speed, when the ball milling time of step S2 changes within 30h to 50h and the ball milling time of step S3 changes within 20h to 30h, increasing the ball milling time is conducive to improving the hydrogen permeability of the high entropy alloy hydrogen permeable membrane. This is attributed to increasing the ball milling speed and ball milling time of the raw metal, which is conducive to reducing the particle size of the metal powder, so that the alloying is more sufficient, the texture of the obtained high entropy alloy hydrogen permeable membrane is more uniform, and the hydrogen permeability is improved.
[0092] Example 10
[0093] A method for preparing a high entropy alloy hydrogen permeable membrane supported by a porous metal tube, which differs from Example 1 in that the atomic percentages of the raw metals cobalt, chromium, iron and nickel are different, specifically: 14.1 at.%, cobalt, 14.1 at.%, chromium, 32.9 at.%, iron, 32.9 at.%, nickel, 3.0 at.%, molybdenum, 3.0 at.%, copper, 100.0 at.%, in total. The remaining operations are the same as those in Example 1, and a high entropy alloy hydrogen permeable membrane is prepared.
[0094] Embodiment 11
[0095] A method for preparing a high entropy alloy hydrogen permeable membrane supported by a porous metal tube, which differs from Example 1 in that the atomic percentages of cobalt, chromium, iron and nickel are different, specifically: 21.3 at.%, cobalt, 21.3 at.%, chromium, 25.7 at.%, iron, 25.7 at.%, nickel, 3.0 at.%, molybdenum, 3.0 at.%, copper, totaling 100.0 at.%. The remaining operations are the same as those in Example 1, and a high entropy alloy hydrogen permeable membrane is prepared.
[0096] Example 12
[0097] A method for preparing a high entropy alloy hydrogen permeable membrane supported by a porous metal tube, which differs from Example 1 in that the atomic percentages of cobalt, chromium, iron and nickel are different, specifically: 32.9 at.%, cobalt, 32.9 at.%, chromium, 14.1 at.%, iron, 14.1 at.%, nickel, 3.0 at.%, molybdenum, 3.0 at.%, copper, 100.0 at.%, in total. The remaining operations are the same as those in Example 1, and a high entropy alloy hydrogen permeable membrane is prepared.
[0098] In Example 1 and Example 10 to Example 12, different atomic percentages of cobalt, chromium, iron and nickel raw metals are used, and the proportions of molybdenum and copper are kept unchanged. High entropy alloy powders are obtained by ball milling, and then high entropy alloy hydrogen permeable membranes are prepared. The prepared high entropy alloy hydrogen permeable membranes extract hydrogen from coke oven gas at 300°C. The hydrogen permeation flux and hydrogen permeation coefficient are summarized in Table 3. The purity of the extracted hydrogen is greater than 99.999%.
[0099] Table 3 Effect of atomic percentage of cobalt, chromium, iron and nickel on high entropy alloy hydrogen permeability membrane
[0100]
[0101] It can be seen from the data in Table 3 that the more the atomic ratio of the raw metals cobalt, chromium, iron and nickel deviates from the equiatomic ratio, the smaller the hydrogen permeation flux and hydrogen permeation coefficient of the prepared high entropy alloy hydrogen permeable membrane, that is, the greater the entropy of the high entropy alloy, the more conducive it is to hydrogen permeation.
[0102] Therefore, the optimal process conditions for preparing a porous metal tube-loaded high-entropy alloy hydrogen permeable membrane with large hydrogen permeation flux and hydrogen permeability coefficient and stable performance are as follows: the raw metals cobalt, chromium, iron and nickel each account for 23.5at.%, and molybdenum and copper each account for 3.0at.%. Molybdenum and copper are first mixed and ball-milled for 50 hours, and then cobalt, chromium, iron and nickel are added and mixed and ball-milled for 30 hours. The ball milling speed is 540r / min, and then the high-entropy alloy powder obtained by ball milling is sprayed onto the surface of a porous Inconel 600 stainless steel tube on a supersonic thermal spraying system to obtain a porous metal tube-loaded CoCrFeNi-MoCu high-entropy alloy hydrogen permeable membrane.
[0103] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a high entropy alloy hydrogen permeable membrane supported by a porous metal tube, characterized in that: The following steps are involved: Under an inert atmosphere, molybdenum and copper are mixed and ball-milled, and then cobalt, chromium, iron and nickel are added and mixed and ball-milled to obtain molybdenum and copper doped cobalt-chromium-iron-nickel high entropy alloy powders. Then, the molybdenum and copper doped cobalt-chromium-iron-nickel high entropy alloy powders are sprayed onto the surface of a porous metal tube by a supersonic thermal spraying film-making method to form a film layer, thereby obtaining a porous metal tube-loaded high entropy alloy hydrogen permeable membrane.
2. The method for preparing a porous metal tube-supported high entropy alloy hydrogen permeable membrane according to claim 1, characterized in that: The atomic percentage of molybdenum and copper in the raw materials is 2 at.% to 4 at.%.
3. The method for preparing a porous metal tube-supported high entropy alloy hydrogen permeable membrane according to claim 1, characterized in that: The mixed ball milling time of molybdenum and copper is 30h-60h, and the ball milling speed is 420r / min-600r / min.
4. The method for preparing a porous metal tube-supported high entropy alloy hydrogen permeable membrane according to claim 1, characterized in that: The atomic percentages of cobalt, chromium, iron and nickel in the raw materials are all 14.1 at.% to 32.9 at.%.
5. The method for preparing a porous metal tube-supported high entropy alloy hydrogen permeable membrane according to claim 1, characterized in that: After molybdenum and copper are ball-milled, cobalt, chromium, iron and nickel are added and the mixed ball-milling time is 20h to 35h, and the ball-milling speed is 420r / min to 600r / min.
6. The method for preparing a porous metal tube-supported high entropy alloy hydrogen permeable membrane according to claim 1, characterized in that: During the process of forming the membrane layer, the average membrane thickness of the high entropy alloy hydrogen permeable membrane is controlled to be 8 μm±1 μm.
7. A porous metal tube-supported high entropy alloy hydrogen permeable membrane, characterized in that: The membrane is prepared by the method for preparing a porous metal tube-supported high entropy alloy hydrogen permeable membrane as claimed in any one of claims 1 to 6.
8. Use of the porous metal tube-supported high entropy alloy hydrogen permeable membrane according to claim 7 in extracting hydrogen from coke oven gas.
Citation Information
Cited By
Composite membrane material as well as preparation method and application thereof
CN121222284A
A composite film material and a preparation method and application thereof
CN121222284B